Respostas

2013-12-07T16:27:33-02:00
 f(x)=1 e f(x)=x²-5x+7
x² - 5x + 7 = 1
x² - 5x + 7 - 1 = 0
x² - 5x + 6 = 0
a = 1       b = - 5         c = 6
∆ = b² - 4 . a . c 
∆ = (- 5)² - 4 . 1 . 6
∆ = 25 - 24
∆ = 1
x =     - b + √∆
        ----------------   
              2
a
x = - (- 5) + 
√1
     ------------------
           2 . 1
x = 5 + 1
     -----------
          2
x' = 5 + 1 
         2
x' = 6 : 2
x' = 3

x" = 5 - 1 
         2
x" = 4 : 2
x" = 2

Raízes: {3, 2}
2013-12-07T17:18:49-02:00
 f(x)=1 e f(x)=x²-5x+7
x
²-5x+7=1
x²-5x+7-1
x²-5x+6=0

Δ=b²-4.a.c
Δ=5²-4.1.6
Δ=25-24
Δ=1

x= -b + √Δ         
        2a
x= -5 + 1
       2.1
x= 5 + 1        x₁= 5+1  6  = 3    
       2                   2        2
                    x₂= 5-1 =  4   = 2
                           2       2
x₁= 3
x₂=2

espero ter ajudado
espero ter ajudado
Ajudou sim! Obg :)